Minimally Invasive Approach to Correct Anomalous Inferior Vena Cava Connection to the Left Atrium. Issue 4 (July 2020) - Pace Napoleone, Carlo; Marini, Davide; Baronetto, Andrea; Deorsola, Luca; Agnoletti, Gabriella; Rinaldi, Mauro
Anomalous drainage of the inferior vena cava into the left atrium is a rare congenital condition. A 20-year-old girl was referred for recurrent transient ischemic attacks. Transthoracic echocardiography revealed a large ostium secundum atrial septal defect, and computed tomography showed anomalous drainage of the inferior vena cava into the left atrium. Through a right mini-thoracotomy, the opening of the inferior vena cava into the atrium was identified under the inferior edge of the interatrial septum, draining into the left atrium, and redirected to the right atrium, using a pericardial patch to reconstruct the atrial septum. Postoperative course was uneventful. Right mini-thoracotomy approach was effective in correcting the anomalous drainage of the inferior vena cava into the left atrium.